2021
DOI: 10.1038/s41416-020-01208-6
|View full text |Cite
|
Sign up to set email alerts
|

Metformin plus lrinotecan in patients with refractory colorectal cancer: a phase 2 clinical trial

Abstract: Background Patients with refractory colorectal (CRC) cancer have few treatment options. This trial tests the combination of metformin and irinotecan in this setting. Methods A phase 2 single-arm trial was conducted, patients received metformin 2500 mg orally a day plus irinotecan 125 mg/m2 intravenously weekly D1 and D8 every 21 days. The primary endpoint was the disease control rate according to the Response Evaluation Criteria in Solid Tumors ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…From other placebo-controlled studies the placebo response rate in this setting was 13% after 12 weeks. In this study 41% reached disease control after 12 weeks, consistent with a beneficial effect of metformin [ 94 ].…”
Section: Cancersupporting
confidence: 82%
“…From other placebo-controlled studies the placebo response rate in this setting was 13% after 12 weeks. In this study 41% reached disease control after 12 weeks, consistent with a beneficial effect of metformin [ 94 ].…”
Section: Cancersupporting
confidence: 82%
“…Findings showing the possible contribution of metformin to reducing the risk of cancer in diabetes patients in 2005 was a prelude to the study of metformin in cancer prevention and treatment [23,27]. A group of clinical trials suggested that metformin showed well-tolerated safe profiles combined with or without traditional or targeted therapies in various cancers [28][29][30][31][32][33][34][35][36]. Clinical applications of metformin in cancer prevention and treatment recently indicated its promising therapeutic effects in colorectal cancer, breast cancer, non-small cell lung cancer, head and neck cancer, and other cancer types, whereas other studies found no beneficial effects in many cancers in non-diabetic patients [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these constraints, electronic health records were used to identify a reduction in cancer-related mortality in patients with diabetes who received treatment with metformin compared with those who did not receive this drug 35 . Observational studies have suggested that patients with diabetes and using metformin have a decreased risk of incident cancer and cancer-related mortality compared with patients not using metformin (reviewed previously 36 , 37 ), and several clinical interventional studies have indicated the beneficial effect of metformin in the treatment of colorectal and ovarian cancers 38 , 39 . Importantly, however, these findings have not been confirmed in prospective, randomized trials.…”
Section: Systematic Drug Repurposingmentioning
confidence: 99%